2010
DOI: 10.1017/s0022215110002410
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of arytenoid asymmetry in relation to vocal symptoms

Abstract: The prevalence of arytenoid asymmetry during adduction is common. The presence of vocal symptoms such as hoarseness, breathiness, inability to project the voice and straining does not generally seem to correlate with the prevalence of arytenoid asymmetry. However, subjects with vocal fatigue are more likely to have cuneiform asymmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…The prevalence of arytenoid adduction asymmetry was 37.1 per cent. 3 In that study, the presence of vocal symptoms did not correlate with the prevalence of arytenoid adduction asymmetry. Husseini et al observed a 50 per cent prevalence of arytenoid adduction asymmetry in a group of healthy singers.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The prevalence of arytenoid adduction asymmetry was 37.1 per cent. 3 In that study, the presence of vocal symptoms did not correlate with the prevalence of arytenoid adduction asymmetry. Husseini et al observed a 50 per cent prevalence of arytenoid adduction asymmetry in a group of healthy singers.…”
Section: Discussionmentioning
confidence: 70%
“…According to our study, the incidence of overriding arytenoids showed a male predominance with a male-to-female ratio of 1.06:1. Hamdan et al and Husseini et al ., 2,3 discovered a male-to-female ratio of 2:1 in their study on arytenoid asymmetry. In the study on arytenoid adduction asymmetry in opera singers, Clarós et al .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations